Recovering phosphorus as struvite from anaerobic digestate of pig manure with ferrochrome slag as a magnesium source - Moyo, L.B.; Simate, G.S.; Mamvura, T.A.; Danha, G. (Elsevier, 2023)
The circular economy initiative has driven the agriculture and agro-based industry to beneficiate from waste,thus closing the material loop towards enhancing economic and environmental performance. In this study, the aim was to recover phosphorus from anaerobic digestate of piggery wastewater (ADPW) using ferrochrome slag (FCSL) as the magnesium source to improve the environmental and economic sustainability of struvite precipitation. This was achieved by leaching 100 g L− 1 of ferrochrome slag with 5 M HCl where 14.02 g L− 1 of magnesium ions were extracted, and this acid-leachate of ferrochrome slag also contained 2650 mg L− 1 of total iron. To simultaneously remove both high concentrations of organic matters in ADPW and iron in FCSL which are known to be detrimental to struvite precipitation, hydrogen peroxide (H2O2) at an H2O2/Fe molar ratio of 0.75 and pH 4.0 was added to the mixture of ADPW and FCSL. After the Fenton reaction, removal efficiencies of chemical oxygen demand (COD) and total iron reached 95.06% and 94.00%, respectively. Then COD and an iron-reduced mixture of ADPW and FCSL were added with a satisfying Mg:N:P molar ratio of 1.2:1:1.15 at pH 9.5 to produce struvite in 1 h. From 1 L of ADPW (2.6 g NH3–N), 0.5 L of FCSL (5.34 g Mg2+), and 6.62 g of PO4 3− P, were consumed to produce 45.57 g of struvite precipitate. Additionally, the economic feasibility of ferrochrome slag was assessed by estimating the chemical costs of FCSL against that of magnesium chloride which is commercially used. It was observed that using FCSL was cheaper as compared to using commercial MgCl2. Response surface methodology coupled with the central composite design was applied as a statistical tool to determine the effects of the key parameters (N:P; Mg:PO4; pH) on phosphorus recovery. Second-order polynomial equations were determined to correlate the parameters. ANOVA was applied and showed that p values for all the investigated parameters were less than 0.05 showing that they had a statistically significant effect on the phosphorus recovery. The study confirmed that it was possible to recover phosphorus as struvite from anaerobic digestate of pig manure with ferrochrome slag as a magnesium source.
Keywords: Anaerobic digestion; Pig manure; Struvite; Ferrochrome slag; Response surface methodology; SDG-9: Industry, innovation and infrastructure; SDG-17: Partnerships for the goals